perencanaan struktur gedung 9 lantai hotel sky sea view jepara - Adi, Ristyanto (Jurnal Civil Engineering Study, 2021)
As part of supporting the tourism sector, the hotel will add to the regional economic value. Based on Indonesian National Standard regulations including: PPIUG 1983, SNI 03-1726 2019, SNI-03-2847, PPPURG, SKSNI-T-15-1991-03 1991. The material uses 30 MPa concrete, the quality of reinforcing steel is 400 MPa. 12 cm thick floor slab with reinforcement X D10-200 and Y D10-200. Roof plate 10 cm thick reinforcement X D10-250 and Y D10-250. Main beam 60x30 cm bearing reinforcement 4D20 field reinforcement 4D20 support stirrup D10-200 field stirrup D10-250 and reinforcement for 4D12. Beam 45x25 cm bearing reinforcement 5D20 field reinforcement 5D20 support stirrup D10-150 field hoop D10-150 and reinforcement for 2D12. Child beam 35x20 cm bearing reinforcement 4D20 field reinforcement 4D20 support stirrup D10-100 field hoop D10-150 and reinforcement for 2D12. Sloof beams 60x30 cm bearing reinforcement 4D20 field reinforcement 4D20 stirrups D10-250 and reinforcement for 4D12. Column 50x50 with 8D20 reinforcement, stirrups D10-200.